Karakteristik fisik silase campuran daun ubikayu (Manihot esculenta) dan rumput Kumpai (Hymenachine ampleexicaulis) - Herlinae Herlinae (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
This study aims to determine the physical characteristics of silage at different mixture levels of cassava leaves (Manihot esculenta) and kumpai grass (Hymenachine ampleexicaulis). The research used Completely Randomized Design (CRD) with treatment A (Without a mixture of cassava leaves), B (Mixture of 10% Cassava Leaves and 90% Kumpai Grass), C (Mixture of 20% Cassava Leaves and 80% Kumpai Grass), D (Mixture of 30% Cassava leaves and 70% Kumpai Grass). The results showed mixture of cassava leaves and kumpai grass silage were influence the characteristic fragrance and no effect on the characteristics of flavor, color and texture of silage. A mixture of 20% cassava leaves and 80% kumpai grass showed the best fragrance with score 24.60 approached a perfect score (25). Key words : Cassava leaves, kumpai grass, silase, physical characteristic